1987
DOI: 10.1136/sti.63.6.386
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis in women attending STD clinic: diagnostic criteria and prevalence of Mobiluncus spp.

Abstract: interest,4 as it has been isolated almost exclusively from women with BV.5 6 In contrast, the first organism associated with BV, Gardnerella vaginalis, has been isolated from about 50% of clinically healthy women.78 The position of Mobi-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1
3

Year Published

1989
1989
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 12 publications
1
22
1
3
Order By: Relevance
“…Stepwise logistic re gression analysis pointed out the presence of > 20 % clue cells in vaginal smear as the independent variable. The presence of clue cells is a reliable marker of bacterial vaginosis [6,18]. Our results imply that it also indicates a high risk of postabortal infection, which is supported by a recent study [19].…”
Section: Discussionsupporting
confidence: 79%
“…Stepwise logistic re gression analysis pointed out the presence of > 20 % clue cells in vaginal smear as the independent variable. The presence of clue cells is a reliable marker of bacterial vaginosis [6,18]. Our results imply that it also indicates a high risk of postabortal infection, which is supported by a recent study [19].…”
Section: Discussionsupporting
confidence: 79%
“…A greater prevalence (from 26% to 36%) has been found in women attending STD clinics [5][6][7][8] than from 11% to 23% in women attending gynaecologic clinics or in other public health structures [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of BV based on Amsel criteria ranges between 24% and 30% in sexually transmitted disease (STD) clinic populations (44)(45)(46), and based on Gram-stained smears, estimates have ranged from 9% (47) to 18% (48) in United Kingdom (UK) clinic-based studies, and have been reported as 29% in a US population-based survey (40) and over 50% in rural Ugandan villages (49). A comparison of Gram stain versus clinical criteria reveals that both are effective for the diagnosis of symptomatic BV; however, the Amsel criteria do not convey information on the composition of vaginal microbiota, and the Gram stain provides only morphological information, which provides limited insight into the composition of the vaginal microbiota.…”
Section: Epidemiology Of Bvmentioning
confidence: 99%